Impact of access to childhood health services on healthy life expectancy of the older population - Liu, Chen; Hou, Xiaochun; Wang, Qiong; Xu, Xinrui; Wu, Bingyi; Liu, Jun (Frontiers in Public Health, 2023)
Background：Life course theory provides new perspectives on the impact of early experiences on health in old age, where unfortunate childhood experiences can alter an individual's health trajectory. This study aims to calculate the healthy life expectancy of the elderly population in China under different childhood experiences, and to explore the influence of childhood medical and health services on the health level of the elderly.Methods ： Differences in healthy life expectancy of the elderly population under different childhood experiences were analyzed using the multi-state life table method to calculate the healthy life expectancy by sex and place of birth, based on the cohort